Adult-onset cerebellar ataxia due to mutations in CABC1/ADCK3. Issue 2 (29th October 2011) - Horvath, Rita; Czermin, Birgit; Gulati, Sweena; Demuth, Stephanie; Houge, Gunnar; Pyle, Angela; Dineiger, Christine; Blakely, Emma L; Hassani, Adam; Foley, Charlotte; Brodhun, Michael; Storm, Karin; et al.
Abstract : Objective: Inherited ataxias are heterogeneous disorders affecting both children and adults. The primary cause can be identified in about half of the patients and only very few can receive causative therapy. Methods: The authors performed sequencing of known Coenzyme Q10 (CoQ10) deficiency genes in 22 patients with unexplained recessive or sporadic ataxia. Results: CABC1/ADCK3 mutations were detected in four patients and two siblings presenting with cerebellar ataxia, epilepsy and muscle symptoms. Spasticity, dystonia, tremor and migraine were variably present; cognitive impairment was severe in early childhood cases, but was absent in adults. In contrast to previous reports, two of the patients had a later-onset, very mild phenotype and remained ambulatory in their late forties. Muscle biopsy revealed lipid accumulation, mitochondrial proliferation and cytochrome c oxidase-deficient fibres, but no typical ragged red fibres. Respiratory-chain enzyme activities and CoQ10 were decreased in severely affected patients but remained normal in a mildly affected patient at 46 years of age. Conclusions: These observations highlight the importance of screening for a potentially treatable cause, CABC1/ADCK3 mutations, not only in severe childhood-onset ataxia, but also in patients with mild cerebellar ataxia in adult life.